Density functional theory calculation of lipophilicity for organophosphate type pesticides - Vlahović Filip; Ivanović Saša; Zlatar Matija; Gruden Maja (Journal of the Serbian Chemical Society, 2017)
Density functional method with continuum solvation model is used for calculation of partition coefficient logKOW and determination of lipophilicity of 22 most frequently used organophosphate type pesticides. Excellent agreement with experimental data is obtained using three different density functional approximations (one local, one general gradient and one hybrid), and our result highlights DFT as a reliable and trustworthy method for calculation and of lipophilicity for this important class of molecules. Furthermore, calculated lipophilicity results are associated with experimentally determined LD50 and LC50 values, showing that the most toxic pesticides are these with transient characteristics (medium lipophilicity), although this concussion must be taken with a caution due to the many factors influencing the ingestion and action of a certain substance in the body beside lipophilicity. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. OI172035 and Grant no. TR31085]